Biomarkers: An Important Tool for Diagnosing and Treating Diabetes Mellitus: Pharmaceutical Sciences-Pharmacy for better health - Chakraborty, Tulshi; Gupta, Sumeet; Saini, Vipin; Talukdar, Arindam (International Journal of Life Science and Pharma Research, 2021)
Diabetes mellitus is a group of metabolic disease caused by an abnormal increase in blood glucose levels due to abnormal activity of pancreatic beta cells. Elevated blood glucose levels causes a variety of cell damage, including endothelial cells, neurons, renal cells, keratinocytes, and fibroblasts. Chronic diabetes mellitus causes several diabetic manifestations such as diabetic neuropathy, diabetic nephropathy, diabetic myopathy, and diabetic dermopathy. There are many causes and risks of diabetes mellitus, including type 1 diabetes caused by bacterial infections, chemical poisoning with food, and self-resistance; Type 2 diabetes is caused by obesity, weight gain, prediabetes and family history, and type 3 is caused by Cushing’s syndrome. Diabetes mellitus treatment has encountered a few progressions in the previous decades with the revelation of explicit prescient prognostic biomarkers that make conceivable the use of individualized treatments. Various hypoglycemic oral and parenteral dosage formulations are used to treat diabetes mellitus, but insulin therapy is one of the most effective treatments for type 1 and type 2 diabetes and its complications. Various conventional diagnosing and treating methods of diabetes mellitus are available but there are limitations of resistance and, accuracy. For that reason now a day’s various biomarkers like Autoantibodies, C-reactive protein (CRP), Fibrinogen, Interleukin-1 receptor antagonist (IL-1RA), Plasminogen activator inhibitor (PAI-1), etc. are used for diagnosis; Adiponectin, microRNA, Acylcarnitine, Haemoglobin A1c, etc. are used for treatment, and 1,5-anhydroglucitol are used for both diagnosis and treatment of diabetes mellitus. In this review, we discussed the functions, application and limitations of diabetes biomarkers in their use as diagnostic and treatment. These biomarkers are of paramount importance in the assessment and diagnosis process, leading to better care and protection of patients. Due to its various advantages, biomarkers are considered as an innovative tool in the advancement of diagnosis and treatment of diabetes mellitus.